If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -3 = 2x + 9 Reorder the terms: -3 + 7x = 2x + 9 Reorder the terms: -3 + 7x = 9 + 2x Solving -3 + 7x = 9 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -3 + 7x + -2x = 9 + 2x + -2x Combine like terms: 7x + -2x = 5x -3 + 5x = 9 + 2x + -2x Combine like terms: 2x + -2x = 0 -3 + 5x = 9 + 0 -3 + 5x = 9 Add '3' to each side of the equation. -3 + 3 + 5x = 9 + 3 Combine like terms: -3 + 3 = 0 0 + 5x = 9 + 3 5x = 9 + 3 Combine like terms: 9 + 3 = 12 5x = 12 Divide each side by '5'. x = 2.4 Simplifying x = 2.4
| y=50-5x | | c-2=3 | | 3n-9=-33 | | 6-z=25+2 | | Y=1100+Y | | 625a+25b+c=35 | | 100=50t | | 3m+(m+5)= | | 20-11=3(x-6) | | 625a+25b+c=25 | | 3z-1=5 | | x^2+11x=-10 | | 13Y=-13 | | 3n+16=20-n | | y^4+9y^3+18y^2= | | 48w-36w=6 | | x^2+x-5= | | s^2+4s+3= | | 7x-13=4x-7 | | m^2+5m-6=0 | | 2x-5=6x-7 | | 4s^2-44s-104= | | 27-(x+12)+17-6= | | 0=420-65t | | 4x-8x=36 | | 3(4z-1)-2(z+8)=2(z+1) | | 12x-17=79 | | x^3-x^2-24x-36=0 | | X^3+X^2-24X-36=0 | | 2-0.83x=-8 | | 0.75x+1=-8 | | 0=-1385n+18790 |